Measurement of the H→WW*→lvlv decay using same-flavour leptons in pp collisions at √s = 13 TeV with the ATLAS detector - Karava, K (2023)
Higgs boson production via gluon-gluon fusion and vector-boson fusion in the $H → WW* → lν lν$ decay mode is measured in the same-flavour channel, where the two leptons are either both electrons or both muons. The proton-proton collision data used in this analysis were produced at the Large Hadron Collider with a centre-of-mass energy of 13 TeV and recorded by the ATLAS detector between 2015 and 2018, corresponding to an integrated luminosity of 139 fb$^{-1}$. This thesis utilizes the traditional cut-based approach, which involves defining event selection criteria purely based on kinematic or geometric observables. The goal of this analysis is to measure the total cross-sections of the gluon-gluon fusion and vector-boson fusion Higgs production modes and compare them to the values predicted by the Standard Model.